Dampak Keteladanan Dan Kompetensi Guru Bagi Motivasi Belajar Siswa Melalui Pendidikan Karakter - Rosari, Veni; Patras, Yuyun Elizabeth; Aziz, Tian Abdul (Universitas Pakuan, 2023)
THE IMPACT OF TEACHER EXEMPLARINESS AND COMPETENCE ON STUDENTS' LEARNING MOTIVATION THROUGH CHARACTER EDUCATIONThis research aims to examine the impact of teacher exemplariness and competence on students' learning motivation through character education, with a focus on the implementation of the honesty canteen program at SDN Kawung Luwuk. In the National Mental Revolution Movement (GNRM), character education is a primary concern to strengthen students' character. Teachers play an important role in setting a good example and designing engaging learning experiences. This research utilizes a descriptive qualitative approach and involves interviews and observations as data collection techniques. The research findings indicate that the implementation of the honesty canteen program at SDN Kawung Luwuk aligns with the school's vision and mission and successfully influences students' learning motivation. Competent teachers who exemplify good behavior play a crucial role in creating a positive learning environment. Students also demonstrate an improvement in their sense of responsibility and integrity. Additionally, the discipline applied in learning and the implementation of moral values through the honesty canteen program contribute to enhancing students' learning motivation. This research provides a better understanding of the importance of character education in shaping students' character and improving their learning motivation. The honesty canteen program at SDN Kawung Luwuk serves as a successful implementation example of character education, which is expected to inspire other schools to develop students' character and enhance their learning motivation.